Homicídio ou feminicídio? : um estudo sobre a transformação da letra morta da lei em práticas sociais - Isabella Silva Matosinhos (2023)
The purpose of this work is to discuss the practices of the actors of the Criminal Justice System who are responsible for classifying a woman's death as “homicide” or “femicide” in Brazil. The research falls within the field of gender studies and institutional administration of conflicts and is based on the assumption that once laws are created – including the Brazilian law on femicide (law n. 13/104/2015) –, they only turn into social practices once they are operationalized. This operationalization process is carried out by subjects who possess their own interests and preconceived notions that guide their practical activities. It is from the operationalization of the law that its instrumental and symbolic effects can emerge. In other words, the meanings and consequences of the law arise from its operationalization process, not from its enactment alone. In order to access the perspectives of the professionals who operationalize the law on femicide, a qualitative methodological approach was used, through semi-structured interviews with men and women occupying the positions of Police, Public Prosecutors, Public Defenders and Judges working in the first instance of the Criminal Justice System in the city of Belo Horizonte, Minas Gerais, Brazil. The main result of the analyses was the identification of the main format of violent death of women classified as femicide by the Justice System: deaths that occur in the domestic/familiar/affectionate context, which do not involve other elements besides the death itself and whose authorship is clear, making further investigation unnecessary. This would be the typical femicide, the normal crime. Consequently, this is the type of case that is most likely to result in a conviction. On the other hand, regarding other events of intentional death of women as a result of gender violence, the further they are from the normal crime model, the harder it is for them to be identified, judged and punished as femicide, which leads them to be classified as other criminal figures, such as homicide. This highlights how (at least part of) the Brazilian Justice System fails to recognize or acknowledge women’s deaths resulting from contempt and discrimination based on their gender, that occur outside the domestic context. Thus, Justice corroborates the logic of the separation between public and private, placing femicide as lethal violence in the private space and other forms of homicide as the lethal violence of public sphere.